ACCUMULATION LEVEL AND POLLUTION STATE OF ZINC (Zn) WITHIN MANGROVE FOREST SEDIMENT AND WATER OF DEMAK COASTAL REGION - Endah Dwi Hastuti (Waste Technology, 2014)
Zinc (Zn) is essential heavy metal for plant growth, but could be lethal for some aquatic organisms. While its accumulation in mangrove ecosystem increased along with the increasing input to the river runoff. This research aimed to observe the concentration of Zn in mangrove sediment and water within mangrove ecosystem in Demak coastal area and its pollution state. This research was conducted through observation involving 4 sampling stations and 3 sampling transects at each station. Data collection including mangrove structure and concentration of Zn in mangrove sediment and water. The result showed that mangrove distribution along Demak coastal area varied among stations. Station 1 and station 2 consist of Avicennia marina only, while station 3 consist of Avicennia marina and Rhizophora mucronata and station 4 consist of Avicennia marina, Rhizophora mucronata and Rhizophora stylosa. Average sediment heavy metal concentration at each station was: 415.81 mg/kg; 561.15 mg/kg; 486.23 mg/kg and 11,507.18 mg/kg respectively. While average heavy metal concentration in mangrove water was 0.12 mg/l; 0.12 mg/l; 0.09 mg/l and 0.17 mg/l respectively. The concentration of heavy metal in mangrove water of Demak region had exceed the maximum limit allowed by the government; while the sediment concentration of heavy metal had exceed tha suitable concentration for organisms.